PrepNet.Br: a Semantic Network for Prepositions - Garcia, Débora D.; Silva, Bento Carlos Dias da (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2015: Anais do X Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2015)
This article presents the idea of the PrepNet.Br, a semantic network consisting of synsets of prepositions to be built for Brazilian Portuguese along the lines of the French PrepNet [Saint-Dizier 2005]. This enterprise is of relevance to the linguistic description of the class of prepositions as well as to Natural Language Processing resource-building. The construction of this network also brings a linguistic analysis alternative to the traditional one, investigating the polysemic nature of prepositions within a cognitive view of language.